Imam Yordan - Yordan, Imam; Heryenzus (SCIENTIA JOURNAL, 2022)
Health is one aspect that determines how high or low the standard of human life is because health is needed to support all activities of a person's life. The establishment of the puskesmas must be a means of administering public and individual health using promotive and preventive methods to achieve the highest degree of public health. The purpose of this study was to analyze the effect of the quality of services and facilities together on patient satisfaction at Tanjung Sengkuang Health Center. The population and sample in this study found 100 respondents with non-probability sampling technique. The data analysis technique in this study used statistical test, classical assumption test, and multiple linear regression analysis,. The results showed, among others: (1) service quality has a good and meaningful impact on patient satisfaction; (2) facilities have a good and meaningful impact on patient satisfaction; (3) the quality of services and facilities simultaneously has q good and meaningful impact on patient satisfaction.